2020
DOI: 10.1111/ajt.15786
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic deprivation is associated with worse patient and graft survival following pediatric liver transplantation

Abstract: Long‐term outcomes remain suboptimal following pediatric liver transplantation; only one third of children have normal biochemical liver function without immunosuppressant comorbidities 10 years posttransplant. We examined the association between an index of neighborhood socioeconomic deprivation with graft and patient survival using the Scientific Registry of Transplant Recipients. We included children <19 years who underwent liver transplantation between January 1, 2008 to December 31, 2013 (n = 2868). Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 42 publications
7
95
0
Order By: Relevance
“…Low socioeconomic status creates a milieu of overlapping barriers that negatively affect long‐term well‐being, such as inadequate nutrition, cost‐related medication underuse, impeded access to medication, fewer learning experiences, housing instability, unemployment, and lack of appropriate social networking, to name just a few 21‐23 . As in our study, Wadhwani et al demonstrated that children from deprived neighborhoods who undergo liver transplantation had worse patient and allograft survival 24 . These investigators postulated that social and economic factors impact long‐term outcome.…”
Section: Discussionsupporting
confidence: 65%
“…Low socioeconomic status creates a milieu of overlapping barriers that negatively affect long‐term well‐being, such as inadequate nutrition, cost‐related medication underuse, impeded access to medication, fewer learning experiences, housing instability, unemployment, and lack of appropriate social networking, to name just a few 21‐23 . As in our study, Wadhwani et al demonstrated that children from deprived neighborhoods who undergo liver transplantation had worse patient and allograft survival 24 . These investigators postulated that social and economic factors impact long‐term outcome.…”
Section: Discussionsupporting
confidence: 65%
“…Our exposures were ecological measures of socioeconomic deprivation and racial segregation. They were measured via an index of area‐based socioeconomic deprivation 28‐30 and a racial index of concentration at the extreme 31 (ICE); both available at census tract and ZCTA levels. The socioeconomic deprivation index is composed of 6 measures from the US Census Bureau's 2015 5‐year American Community Survey (ACS): median household income, and fraction of the population below the federal poverty level, adults with a high school education, households receiving public assistance, population with no health insurance, and housing units that are vacant 28 .…”
Section: Methodsmentioning
confidence: 99%
“…In “Neighborhood Socioeconomic Deprivation Is Associated with Worse Patient and Graft Survival Following Pediatric Liver Transplantation,” Wadhwani et al used the Nationwide Community Deprivation Index, which is based on the US Census Bureau‐administered American Community Survey. The calculations of neighborhood socioeconomic deprivation are based on the home zip code at the time of transplant as reported to Scientific Registry of Transplant Recipients.…”
mentioning
confidence: 99%